2001
DOI: 10.1016/s0020-7292(01)00426-x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring obstetric services: putting the UN guidelines into practice in Malawi. I: developing the system

Abstract: The UNICEF/WHO/ UNFPA "Guidelines for Monitoring the Availability and Use of Obstetric Services" was published in 1997 as a guide for implementing process indicators. The Malawi Safe Motherhood Project covers 5 million people and was the first large project to introduce the new indicators as part of a routine monitoring system. A rigorous process of needs assessment, tools development, operations research, field testing and training was conducted. It was necessary to reach agreement on locally appropriate stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…These indicators have been used to assess services available at selected hospitals in other countries [4]. In fact, as early as 1998, the Malawi Safe Motherhood Project introduced these indicators throughout the Southern Region of the country as part of a routine monitoring system, and collected and analyzed data for 3 consecutive years following its introduction [5,6]. Our study confirmed that for most indicators, the Malawi health system did not meet the recommended levels.…”
Section: Resultsmentioning
confidence: 57%
“…These indicators have been used to assess services available at selected hospitals in other countries [4]. In fact, as early as 1998, the Malawi Safe Motherhood Project introduced these indicators throughout the Southern Region of the country as part of a routine monitoring system, and collected and analyzed data for 3 consecutive years following its introduction [5,6]. Our study confirmed that for most indicators, the Malawi health system did not meet the recommended levels.…”
Section: Resultsmentioning
confidence: 57%
“…Under-reporting of obstetric emergencies and over-reporting due to double counting have been observed in a system developed to monitor obstetric services in Malawi 22 . A comprehensive parallel data collection, as the one instituted in this study may be more reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Goodburn et al used a prospective cohort design to study the effectiveness of TBA training in preventing postpartum infection in Bangladesh (35). The percentage of TBAs who practiced the “three cleans” (hands, surface and umbilical cord) was significantly higher among the trained group (45 vs. 19%), but there was no significant reduction in the incidence of postpartum infections.…”
Section: Resultsmentioning
confidence: 99%